2015
DOI: 10.1016/j.dsr2.2013.12.001
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of satellite-derived sea surface temperature fronts using two edge detection algorithms

Abstract: Satellite-derived sea surface temperature (SST) fronts provide a valuable resource for the study of oceanic fronts. Two edge detection algorithms designed specifically to detect fronts in satellite-derived SST fields are compared: the histogram-based algorithm of Cayula and Cornillon (1992, 1995) and the entropy-based algorithm of Shimada et al. (2005). The algorithms were applied to four months (July and August for both 1995 and 1996) of SST fields and the results are compared with SST data taken by the M.V. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…The JSD method does not only diminish the influence of impulsive noise but also discerns the finer-scale curvilinear frontal features in coastal regions due to its independence from temporal or spatial variations of geophysical parameters [11]. Its effectiveness was already proven by Shimada et al [11], and Chang and Cornillon [56] through comparison with other traditional methods (e.g., gradient magnitude and histogram edge detection algorithms) using the SST images, and the results showed that the entropy-based algorithm had better performance, especially for detecting short and weak fronts. Here, the JSD was calculated from four JSD matrices that were estimated in each of two 5ˆ5 pixel TSM subwindows with four different directions (horizontal, vertical, and two diagonals, shown in [11]).…”
Section: Water Turbidity Front Retrievalmentioning
confidence: 77%
“…The JSD method does not only diminish the influence of impulsive noise but also discerns the finer-scale curvilinear frontal features in coastal regions due to its independence from temporal or spatial variations of geophysical parameters [11]. Its effectiveness was already proven by Shimada et al [11], and Chang and Cornillon [56] through comparison with other traditional methods (e.g., gradient magnitude and histogram edge detection algorithms) using the SST images, and the results showed that the entropy-based algorithm had better performance, especially for detecting short and weak fronts. Here, the JSD was calculated from four JSD matrices that were estimated in each of two 5ˆ5 pixel TSM subwindows with four different directions (horizontal, vertical, and two diagonals, shown in [11]).…”
Section: Water Turbidity Front Retrievalmentioning
confidence: 77%
“…Singularity exponents characterize the scaling at small scales, are independent of the gradient magnitude, and measure the degree of continuity of the field. Moreover, singularity exponents have the advantage over other popular approaches for detecting fronts, such as those based on histograms or gradient filters like the Sobel filter (Chang & Cornillon, 2015; Kirches et al., 2016), that they can be easily connected to statistical quantities that are central to turbulence theories (Section 2). Indeed, the singularity spectrum, which gives the fractal dimension of those points with the same exponent, emerges as a fundamental property of the ocean providing the link between anomalous scaling and the intensity of fronts.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it should be pointed out that previous studies in this region have applied different detection methods to identify fronts in satellite SST observations. To evaluate those methods, Ullman and Cornillon (2000) and Chang and Cornillon (2015) applied an along‐track gradient algorithm to detect fronts in Oleander temperature observations similar to the method used here to detect fronts in salinity. In future work, some of the methods already developed to detect fronts in SST could be adapted to detect fronts in the 2D reconstructed SSS fields.…”
Section: Conclusion and Discussionmentioning
confidence: 99%